FILTR USKUNASINING TOZALASH BARABANINI AYLANISHLAR SONINI ANIQLASH (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
In the course of the experiments, the following method was developed to determine the initial speed of the number of revolutions of the cleaning filter drum. The selected fabric was installed and dusty air was sent, where the amount of dust at the inlet and outlet of the device was measured, in addition, the air velocities were measured at the inlet and outlet. It is required to clean the fabric surface within 30 seconds of the filter's operation time in dust.